Preparation method of lithium iron phosphate lithium ion battery and lithium iron phosphate lithium ion battery
By modifying the graphite materials obtained by natural graphite raw materials and adding specific additives to the electrolyte, the improvement space for lithium iron phosphate lithium ion batteries in terms of energy density, low temperature resistance and charging performance is solved, and high energy density is achieved. Fast charging and excellent low-temperature performance battery.
Patent Information
- Application Number
- CN202411667642.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-21
AI Technical Summary
The existing lithium iron phosphate lithium-ion batteries have room for improvement in energy density, low temperature resistance and charging performance.
The graphite material modified from natural graphite raw materials is used as the negative electrode active material, and additives such as vinyle carbonate are added to the electrolyte to improve the film forming performance and stability of the electrolyte and improve the low-temperature performance and cycling performance of the battery. .
The energy density, low-temperature performance and charging speed of lithium iron phosphate lithium-ion batteries are improved, ensuring that lithium ions are embedded and removed smoothly at low temperatures, reducing lithium ion consumption and increase battery internal resistance during charging.
Smart Images

Figure CN119495828A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a preparation method of a lithium iron phosphate lithium ion battery and a lithium iron phosphate lithium ion battery. Background Art
[0002] With the rapid development of new energy vehicles, energy storage power stations and other industries, lithium iron phosphate batteries have been widely used due to their high safety, long life and good environmental performance. However, the lithium iron phosphate lithium ion batteries in the prior art still need to be improved in terms of energy density, low temperature resistance and charging performance. Therefore, it is very important to provide a preparation method of a lithium iron phosphate lithium ion battery with high energy density, good low temperature resistance and fast charging speed, and a lithium iron phosphate lithium ion battery. Summary of the invention
[0003] The purpose of the present invention is to solve the above problems and provide a method for preparing a lithium iron phosphate lithium ion battery and a lithium iron phosphate lithium ion battery. The preparation method can obtain a lithium iron phosphate lithium ion battery with high energy density, good low temperature resistance and fast charging speed.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0005] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate lithium ion battery, comprising the steps of:
[0006] Providing negative electrode materials: the negative electrode materials use graphite materials obtained by modifying natural graphite raw materials as negative electrode active materials;
[0007] An electrolyte is provided: the electrolyte comprises an organic solvent containing a first additive, a lithium salt and a second additive; in terms of mass percentage, the electrolyte comprises 10%-13% of a lithium salt, 75%-85% of an organic solvent and 3%-8% of a second additive, and the amount of the first additive added to the organic solvent is 2.5%-4%; wherein the first additive comprises one or more of vinylene carbonate, vinyl ethylene carbonate or cyclic disulfonate, and the first additive is used to improve the film-forming performance and stability of the electrolyte, and improve the low temperature performance and cycle performance of the battery.
[0008] Optionally, the first additive includes vinyl ethylene carbonate and cyclic disulfonate.
[0009] Optionally, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonate)imide or lithium difluorobis(oxalate)borate; and / or, the second additive includes one or more of vinyl ethylene carbonate, fluoroethylene carbonate, propane sultone, ethyl propionate or sulfonate additives.
[0010] Optionally, the negative electrode active material is a coated graphite material, and the negative electrode active material is prepared by coating the natural graphite raw material; specifically comprising the steps of:
[0011] Raw material mixing: mixing natural graphite raw material and nano sol in a mass ratio of 8:1-10:1 to obtain a first product; the nano sol includes one or more of nano aluminum sol, nano zirconium sol or nano titanium sol;
[0012] Spheroidization treatment: the first product obtained after the raw materials are mixed is subjected to spheroidization treatment to obtain the second product;
[0013] Carbonization treatment: The obtained second product is subjected to carbonization treatment in a protective atmosphere to obtain a coated graphite negative electrode active material.
[0014] Optionally, the negative electrode active material is a fluorine-doped modified graphite material, which is obtained by doping and modifying natural graphite raw materials; the doping and modification treatment specifically includes the following steps:
[0015] Providing raw materials: providing natural graphite raw materials; providing dopant emulsion, wherein the solid content of the dopant emulsion is 20-30wt%, and the dopant emulsion comprises at least one of polyperfluoroethylene emulsion and polytetrafluoroethylene emulsion;
[0016] Mixing and dispersing: mixing the natural graphite raw material and the dopant emulsion at a mass ratio of 8:1 and stirring to obtain a third product;
[0017] Drying: drying the obtained third product at 105±5°C for 10-14 hours to remove moisture and solvent in the material to obtain a fourth product;
[0018] Sintering treatment: The fourth product is sintered in a sealed chamber under a protective atmosphere to obtain a fluorine-doped modified graphite negative electrode material.
[0019] Optionally, the preparation method further comprises the steps of:
[0020] Providing a positive electrode material: the positive electrode material uses carbon-coated lithium iron phosphate as a positive electrode active material: the carbon-coated lithium iron phosphate is prepared by any one of a high-temperature solid phase synthesis method, a coprecipitation method, a sol-gel method or a hydrothermal method;
[0021] A diaphragm is provided: the diaphragm comprises a ceramic diaphragm with double-sided coating.
[0022] In a second aspect, the present invention provides a lithium iron phosphate lithium ion battery, which is prepared by the preparation method of lithium iron phosphate lithium ion as described above.
[0023] Optionally, the lithium iron phosphate lithium-ion battery includes a positive electrode material, a negative electrode material, a diaphragm and an electrolyte; the positive electrode material uses lithium iron phosphate as the positive electrode active material, the negative electrode material uses a graphite material modified from a natural graphite material as the negative electrode active material, the diaphragm includes a ceramic coating diaphragm, and the electrolyte includes an organic solvent containing a first additive, a lithium salt and a second additive; wherein the first additive includes one or more of vinylene carbonate, vinyl ethylene carbonate or cyclic disulfonate.
[0024] Optionally, the electrolyte includes, by mass percentage, 10%-13% of lithium salt, 75%-85% of organic solvent and 3%-8% of a second additive, and the amount of the first additive added to the organic solvent is 2.5%-4%.
[0025] Optionally, the negative electrode active material includes a coated graphite material obtained by coating a natural graphite material, or a fluorine-doped modified graphite material obtained by doping and modifying a natural graphite material.
[0026] The beneficial effects produced by the present invention include at least:
[0027] In the preparation method of the lithium iron phosphate lithium ion battery of the present invention, on the one hand, the negative electrode material adopts the graphite material obtained by modifying the natural graphite raw material as the negative electrode active material, and the interlayer spacing of the graphite material is expanded to a certain extent by modifying the natural graphite raw material, which is conducive to the subsequent embedding and extraction of lithium ions, thereby improving the specific capacity of the negative electrode material, and then improving the energy density of the lithium ion battery; at the same time, the conductivity of the graphite material at low temperature is improved, ensuring that lithium ions can also be smoothly embedded and extracted at low temperatures, and improving the low temperature performance of the lithium ion battery; on the other hand, the electrolyte includes an organic solvent containing a first additive, and the use of the first solvent can form a more stable and dense SE I film on the surface of the negative electrode material, reduce the consumption of lithium ions during charging and the increase of the internal resistance of the battery, and is conducive to fast charging; at the same time, it can also inhibit the side reaction of the electrolyte with the electrode material during the charging and discharging process, reduce gas generation and battery capacity attenuation, maintain the stability of the battery under high rate charging and discharging, and then accelerate the charging speed; at the same time, the vinyl ethylene carbonate in the first additive can also improve the low temperature performance of the lithium ion battery to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The charge and discharge cycle performance comparison curve of the lithium iron phosphate lithium ion battery obtained in Example 1 and the charge and discharge cycle performance comparison curve of the lithium iron phosphate lithium ion battery obtained in Comparative Example 1;
[0029] Figure 2It is a comparison curve diagram of the charge and discharge cycle performance of the lithium iron phosphate lithium ion battery obtained in Example 2 and the charge and discharge cycle performance of the lithium iron phosphate lithium ion battery obtained in Comparative Example 1. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described in the present invention. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0031] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0032] In the present invention, descriptions such as “first”, “second”, etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features.
[0033] Unless otherwise specified, the raw materials involved in the present invention can be sourced from suppliers known in the art, or prepared by known methods.
[0034] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate lithium ion battery, comprising the steps of:
[0035] Providing negative electrode materials: the negative electrode materials use graphite materials obtained by modifying natural graphite raw materials as negative electrode active materials;
[0036] An electrolyte is provided: the electrolyte comprises an organic solvent containing a first additive, a lithium salt and a second additive; in terms of mass percentage, the electrolyte comprises 10%-13% of a lithium salt, 75%-85% of an organic solvent and 3%-8% of a second additive, and the amount of the first additive added to the organic solvent is 2.5%-4%; wherein the first additive comprises one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC) or a cyclic disulfonic acid ester, and the first additive is used to improve the film-forming performance and stability of the electrolyte, and improve the low temperature performance and cycle performance of the battery.
[0037] In the preparation method of the lithium iron phosphate lithium-ion battery of the present invention, on the one hand, the negative electrode material adopts the graphite material obtained by modifying the natural graphite raw material as the negative electrode active material. By modifying the natural graphite raw material, the interlayer spacing of the graphite material is expanded to a certain extent, which is conducive to the subsequent embedding and extraction of lithium ions, thereby improving the specific capacity of the negative electrode material, and then improving the energy density of the lithium ion battery; at the same time, the conductivity of the graphite material at low temperature is improved, ensuring that lithium ions can be smoothly embedded and extracted at low temperatures, and improving the low temperature performance of the lithium ion battery; on the other hand, the electrolyte includes an organic solvent containing a first additive, and the use of the first solvent can form a more stable and dense SE on the surface of the negative electrode material. I film, reduces the consumption of lithium ions and the increase of battery internal resistance during charging, which is conducive to fast charging; at the same time, it can also inhibit the side reaction between the electrolyte and the electrode material during charging and discharging, reduce gas generation and battery capacity attenuation, maintain the stability of the battery under high-rate charging and discharging, and thus accelerate the charging speed; at the same time, vinyl ethylene carbonate (VEC) in the first additive can also improve the low-temperature performance of lithium-ion batteries to a certain extent.
[0038] In some embodiments, the first additive includes vinyl ethylene carbonate (VEC) and cyclic disulfonate; in terms of mass fractions, the ratio of the addition amount of vinyl ethylene carbonate (VEC) and the cyclic disulfonate in the first additive is 9:1 to 7:3. Among them, vinyl ethylene carbonate (VEC) is mainly used as a film-forming additive in lithium-ion battery electrolytes. It can form a thin film in the electrolyte of the battery, namely the solid electrolyte interface film (SEI film). This film can prevent the lithium ions in the electrolyte from directly contacting the negative electrode material, thereby preventing short circuits and improving the safety of the battery. The addition of VEC can significantly improve the cycle stability and capacity retention rate of the battery. It can also improve the low-temperature performance of the battery to a certain extent, so that the battery can maintain good charge and discharge performance at lower temperatures; while cyclic bicyclic acid esters can form a solid electrolyte interface film (SEI film) on the surface of the battery electrode in the electrolyte. This film is denser and more stable, and can effectively inhibit the co-embedding and reduction decomposition of solvent molecules in the negative electrode, thereby improving the cycle performance and high-temperature performance of the battery, and can improve the cycle stability of lithium-ion batteries and reduce capacity decay. The mixed use of vinyl ethylene carbonate (VEC) and cyclic disulfonate can form a more stable and dense SEI film on the surface of the negative electrode, reduce the consumption of lithium ions and the increase of battery internal resistance during charging, and facilitate fast charging; at the same time, it can also inhibit the side reaction between the electrolyte and the electrode material during the charging and discharging process, reduce gas generation and battery capacity attenuation, maintain the stability of the battery under high-rate charging and discharging, and thus increase the charging speed.
[0039] Optionally, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonate)imide or lithium difluorobis(oxalate)borate; and / or, the second additive includes one or more of vinyl ethylene carbonate, fluoroethylene carbonate, propane sultone, ethyl propionate or sulfonate additives. The electrolyte described in the present invention includes a first additive and a second additive. When the sulfonate additive in the second additive is used in combination with vinyl carbonate (VC) and / or vinyl ethylene carbonate (VEC) in the first additive, a synergistic effect can be produced to further improve the cycle performance of the battery and inhibit the gas production characteristics. This synergistic effect is achieved through the interaction between different additives. The combined use of multiple additives makes the overall performance of the battery better than the effect of using any one additive alone.
[0040] In some embodiments, the negative electrode active material is a coated graphite material, and the negative electrode active material is prepared by coating the natural graphite raw material; specifically comprising the steps of:
[0041] Raw material mixing: mixing natural graphite raw material and nano sol in a mass ratio of 8:1-10:1 to obtain a first product; the nano sol includes one or more of nano aluminum sol, nano zirconium sol or nano titanium sol;
[0042] Spheroidization treatment: the first product obtained after the raw material mixing is subjected to spheroidization treatment to obtain the second product; the spheroidization treatment is used to further spheroidize the graphite particles in the first product and ensure that the nanosol is evenly coated on the surface of the graphite particles; the spheroidization treatment is also carried out in the air flow vortex micro-powder machine. Specifically, after the raw material mixing is completed, the rotation speed and air volume of the classifying wheel and the spheroidizing wheel of the air flow vortex micro-powder machine are continuously adjusted to obtain the second product;
[0043] Carbonization treatment: In a protective atmosphere, the obtained second product is subjected to carbonization treatment to obtain a coated graphite negative electrode active material. Specifically, the carbonization treatment is carried out in a box-type carbonization furnace; the temperature rise curve of the carbonization treatment is: heating to 500°C at a heating rate of 2°C / min, and maintaining the temperature at this temperature for 2 hours; then heating to 1000°C at a heating rate of 5°C / min, and maintaining the temperature at this temperature for 2 hours; naturally cooling to room temperature and then taking out to obtain a graphite material with preliminary coating treatment, and the obtained graphite material with preliminary coating treatment is dispersed to break up the agglomerates that may be formed, and then sieving is performed to obtain a coated graphite negative electrode material of preset specifications. Before the carbonization treatment, the second product obtained after the spheroidization treatment is also screened.
[0044] In another embodiment, the negative electrode active material is a fluorine-doped modified graphite material, which is obtained by doping and modifying natural graphite raw materials; the doping and modification treatment specifically includes the steps of:
[0045] Providing raw materials: providing natural graphite raw materials; providing dopant emulsion, wherein the solid content of the dopant emulsion is 20-30wt%; the dopant emulsion comprises at least one of polyperfluoroethylene emulsion or polytetrafluoroethylene emulsion; specifically, the solid content of the dopant emulsion is 25wt%;
[0046] Mixing and dispersing: The natural graphite raw material and the dopant emulsion are mixed and stirred at a mass ratio of 8:1 to obtain a third product; stirring is performed during the mixing of the raw materials to improve the uniformity of the raw material mixing; optionally, the stirring is performed using a magnetic stirrer for 1-2 hours so that the natural graphite raw material and the dopant emulsion can be mixed uniformly. It can be understood that the stirring time listed in the present invention cannot be used as the only limitation on the stirring time, and the stirring time can be specifically selected according to actual conditions; further, anhydrous ethanol is added during the mixing of the natural graphite raw material and the dopant emulsion to promote dissolution;
[0047] Sintering treatment: The fourth product is sintered in a sealed chamber under a protective atmosphere to obtain a fluorine-doped modified graphite negative electrode material. The sintering temperature is 400°C and the sintering time is 5 hours to ensure that the doping elements can be evenly distributed in the graphite matrix and chemically react; after the sintering treatment, the product obtained after the sintering treatment is screened to remove impurities and incompletely reacted particles to obtain a fluorine-doped modified graphite negative electrode material.
[0048] The preparation method further comprises the steps of:
[0049] Providing a positive electrode material: the positive electrode material uses carbon-coated lithium iron phosphate as a positive electrode active material;
[0050] The carbon-coated lithium iron phosphate is prepared by any one of a high-temperature solid phase synthesis method, a coprecipitation method, a sol-gel method or a hydrothermal method;
[0051] A separator is provided: the separator includes a ceramic separator with double-sided coating to improve the safety and electrochemical stability of the battery.
[0052] Specifically, the diaphragm includes a ceramic base layer and a rubber coating layer coated on both sides of the ceramic base layer; in some embodiments, the thickness of the ceramic base layer is 3 mm, and the thickness of the rubber coating layer is 1 mm. Further optionally, the rubber coating layer can be a PE rubber layer.
[0053] In the present invention, the carbon-coated lithium iron phosphate is prepared by a high-temperature solid phase synthesis method. In the process of preparing the carbon-coated lithium iron phosphate positive electrode material by the high-temperature solid phase synthesis method, the heat released when the carbon source is decomposed is mainly used to promote the reaction at a relatively low temperature. The preparation of the lithium iron phosphate positive electrode material by the high-temperature solid phase synthesis method includes the following steps: mixing a lithium source, an iron source and a phosphorus source to obtain a first reaction system, mixing the first reaction system with a carbon source to obtain a carbon-coated lithium iron phosphate precursor, and mixing by ball milling; calcining the obtained carbon-coated lithium iron phosphate precursor in a staged manner to obtain a lithium iron phosphate positive electrode material; wherein the reaction temperature of the staged calcination is in the range of 600-800°C, and the reaction time is 6-9h. Specifically, the temperature change curve of the segmented calcination is as follows: the carbon-coated lithium iron phosphate precursor is first calcined at 600°C for 4 hours, then heated to 700°C for 3 hours, and then heated to 800°C for 2 hours. After the segmented calcination, the obtained material is sieved to obtain lithium iron phosphate powder with uniform particle size distribution. The crystal structure of the lithium iron phosphate material obtained after such treatment is more uniform and stable. By controlling the reaction temperature and time during the preparation process, the material decomposition or structural damage caused by excessive temperature is avoided.
[0054] In a second aspect, a lithium iron phosphate lithium-ion battery is provided, which is prepared by the preparation method of lithium iron phosphate lithium-ion as described above; the lithium iron phosphate lithium-ion battery comprises a positive electrode material, a negative electrode material, a diaphragm and an electrolyte; the positive electrode material adopts lithium iron phosphate (LiFePO4) as the positive electrode active material, the negative electrode material adopts a graphite material modified from a natural graphite material as the negative electrode active material, the diaphragm comprises a ceramic coating diaphragm, and the electrolyte comprises an organic solvent containing a first additive, a lithium salt and a second additive; wherein the first additive comprises one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC) or a cyclic disulfonate.
[0055] In terms of mass percentage, the electrolyte includes 10%-13% of lithium salt, 75%-85% of organic solvent and 3%-8% of second additive, and the amount of the first additive added to the organic solvent is 2.5%-4%.
[0056] Optionally, the negative electrode active material includes a coated graphite material obtained by coating a natural graphite material, or a fluorine-doped modified graphite material obtained by doping and modifying a natural graphite material; the electrochemical performance and stability of the negative electrode material are improved by coating or doping modification.
[0057] Furthermore, the lithium iron phosphate lithium-ion battery also includes a shell, the shell contains a battery cell, the electrolyte is filled in the shell, the battery cell includes a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet includes a conductive agent, an adhesive and the positive electrode material as described above, and the negative electrode sheet includes a conductive agent, an adhesive and the negative electrode material as described above.
[0058] Example 1
[0059] The lithium iron phosphate lithium-ion battery comprises a positive electrode material, a negative electrode material, a diaphragm and an electrolyte, wherein the positive electrode material adopts carbon-coated lithium iron phosphate as a positive electrode active material, the carbon-coated lithium iron phosphate is prepared by the preparation method as described above, and the negative electrode material adopts a coated graphite material prepared by coating a natural graphite material as a negative electrode active material; the electrolyte adopts a system consisting of an organic solvent, a lithium salt and an additive containing vinyl carbonate (VC) and a cyclic disulfonate additive, and the diaphragm adopts a ceramic diaphragm with double-sided glue coating. Specifically, in the raw material mixing step, the natural graphite raw material and the nanosol are mixed at a mass ratio of 8:1, and the natural graphite raw material and the nanosol are mixed in an airflow vortex micro-powder machine, and the mixing is mixed for 2 hours under the condition of a classification wheel speed of 800r / min, so that the nanosol is evenly distributed on the surface of the scale structure of the natural graphite raw material.
[0060] The positive electrode material and the negative electrode material are made into a positive electrode sheet and a negative electrode sheet respectively, and then the positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 205Ah battery cell as a test sample.
[0061] Example 2
[0062] The lithium iron phosphate lithium-ion battery includes a positive electrode material, a negative electrode material, a separator and an electrolyte. The positive electrode material uses carbon-coated lithium iron phosphate as a positive electrode active material, and the carbon-coated lithium iron phosphate is prepared by the preparation method described above. The negative electrode material uses a doped graphite material prepared by fluorine doping and modification of natural graphite as a negative electrode active material; the electrolyte uses an organic solvent containing vinyl carbonate (VC) and cyclic disulfonate additives, a lithium salt and an additive system, and the separator uses a double-sided glue-coated ceramic separator. Example 2 Except for the different negative electrode active materials selected, the other preparation conditions are the same as Example 1.
[0063] The positive electrode material and the negative electrode material are made into a positive electrode sheet and a negative electrode sheet respectively, and then the positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 205Ah battery cell as a test sample.
[0064] Comparative Example 1:
[0065] The lithium iron phosphate lithium-ion battery includes a positive electrode material, a negative electrode material, a separator and an electrolyte; compared with Example 1, the difference of Comparative Example 1 is that the negative electrode material in Comparative Example 1 uses natural graphite material as a negative electrode active material; the electrolyte uses a system consisting of an organic solvent, a lithium salt and an additive that does not contain vinylene carbonate (VC) and a cyclic disulfonate additive, and the separator uses a ceramic separator with double-sided glue coating. Except for the different negative electrode active materials and electrolytes selected in Comparative Example 1, other preparation conditions are the same as those of Example 1.
[0066] The positive electrode material and the negative electrode material are made into a positive electrode sheet and a negative electrode sheet respectively, and then the positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 205Ah battery cell as a test sample.
[0067] The test samples obtained in Example 1, Example 2 and Comparative Example 1 were respectively tested for normal temperature and low temperature charge and discharge cycle performance, capacity, etc.
[0068] Depend on Figure 1 As shown in Table 1 below, compared with Comparative Example 1, the energy density of Example 1 is increased by 2.76%, and the low temperature 5°C capacity retention rate is increased by 7%; Figure 1 It can be seen from the comparison cycle curves that under the condition of charge and discharge at room temperature 25°C and 0.5C, the capacity retention rate curve platform of Example 1 is above that of Comparative Example 1. Judging from its trend, the cycle life is better than that of Comparative Example 1.
[0069] Table 1. Comparison table of performance tests of the test samples of Example 1 and Comparative Example 1.
[0070]
[0071] Depend on Figure 2 As shown in Table 2 below, compared with Comparative Example 1, the energy density of Example 2 is increased by 3.25%, and the low temperature 5°C capacity retention rate is increased by 5.85%. Figure 2 It can be seen intuitively from the cycle curve that at room temperature 25°C and 0.5C charge and discharge conditions, the capacity retention rate curve platform of Example 2 is above that of Comparative Example 1. Judging from its trend, the cycle life is better than that of Comparative Example 1.
[0072] Table 2. Comparative table of performance tests of the test samples of Example 2 and Comparative Example 1.
[0073]
[0074] In summary, the lithium iron phosphate lithium-ion battery prepared by the technical solution of the present invention has high energy density, fast charging and excellent low-temperature performance.
[0075] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0076] The above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium iron phosphate lithium-ion battery, characterized in that: Includes steps: Providing negative electrode materials: the negative electrode materials use graphite materials obtained by modifying natural graphite raw materials as negative electrode active materials; An electrolyte is provided: the electrolyte includes an organic solvent containing a first additive, a lithium salt and a second additive; in terms of mass percentage, the electrolyte includes 10%-13% of a lithium salt, 75%-85% of an organic solvent and 3%-8% of a second additive, and the amount of the first additive added to the organic solvent is 2.5%-4%; wherein the first additive includes one or more of vinylene carbonate, vinyl ethylene carbonate or cyclic disulfonate.
2. The method for preparing a lithium iron phosphate lithium-ion battery according to claim 1, characterized in that: The first additive includes vinyl ethylene carbonate and cyclic disulfonate.
3. The method for preparing a lithium iron phosphate lithium-ion battery according to claim 1, characterized in that: The lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonate)imide or lithium difluorobis(oxalate)borate; and / or the second additive includes one or more of vinyl ethylene carbonate, fluoroethylene carbonate, propane sultone, ethyl propionate or sulfonate additives.
4. The method for preparing a lithium iron phosphate lithium-ion battery according to claim 1, characterized in that: The negative electrode active material is a coated graphite material, and the negative electrode active material is prepared by coating the natural graphite raw material; specifically comprising the steps of: Raw material mixing: mixing natural graphite raw material and nano sol in a mass ratio of 8:1-10:1 to obtain a first product; the nano sol includes one or more of nano aluminum sol, nano zirconium sol or nano titanium sol; Spheroidization treatment: the first product obtained after the raw materials are mixed is subjected to spheroidization treatment to obtain the second product; Carbonization treatment: The obtained second product is subjected to carbonization treatment in a protective atmosphere to obtain a coated graphite negative electrode active material.
5. The method for preparing a lithium iron phosphate lithium-ion battery according to claim 1, characterized in that: The negative electrode active material is a fluorine-doped graphite material, which is obtained by doping and modifying natural graphite raw materials; the doping and modification treatment specifically includes the following steps: Providing raw materials: providing natural graphite raw materials; providing dopant emulsion, wherein the solid content of the dopant emulsion is 20-30wt%, and the dopant emulsion comprises at least one of polyperfluoroethylene emulsion and polytetrafluoroethylene emulsion; Mixing and dispersing: mixing the natural graphite raw material and the dopant emulsion at a mass ratio of 8:1 and stirring to obtain a third product; Drying: drying the obtained third product at 105±5°C for 10-14 hours to remove moisture and solvent in the material to obtain a fourth product; Sintering treatment: The fourth product is sintered in a sealed chamber under a protective atmosphere to obtain a fluorine-doped modified graphite negative electrode material.
6. The method for preparing a lithium iron phosphate lithium-ion battery according to claim 1, characterized in that: The preparation further comprises the steps of: Providing a positive electrode material: the positive electrode material uses carbon-coated lithium iron phosphate as a positive electrode active material: the carbon-coated lithium iron phosphate is prepared by any one of a high-temperature solid phase synthesis method, a coprecipitation method, a sol-gel method or a hydrothermal method; A diaphragm is provided: the diaphragm comprises a ceramic diaphragm with double-sided coating.
7. A lithium iron phosphate lithium ion battery, characterized in that: The lithium iron phosphate is prepared by the preparation method of lithium iron phosphate according to any one of claims 1 to 6.
8. The lithium iron phosphate lithium ion battery according to claim 7, characterized in that: It includes a positive electrode material, a negative electrode material, a separator and an electrolyte; the positive electrode material uses carbon-coated lithium iron phosphate as the positive electrode active material, the negative electrode material uses a graphite material modified from a natural graphite material as the negative electrode active material, the separator includes a ceramic coating separator, and the electrolyte includes an organic solvent containing a first additive, a lithium salt and a second additive; wherein the first additive includes one or more of vinylene carbonate, vinyl ethylene carbonate or cyclic disulfonate.
9. The lithium iron phosphate lithium-ion battery according to claim 8, characterized in that: In terms of mass percentage, the electrolyte includes 10%-13% of lithium salt, 75%-85% of organic solvent and 3%-8% of second additive, and the amount of the first additive added to the organic solvent is 2.5%-4%.
10. The lithium iron phosphate lithium ion battery according to claim 7, characterized in that: The negative electrode active material includes a coated graphite material obtained by coating a natural graphite material, or a fluorine-doped modified graphite material obtained by doping and modifying a natural graphite material.